From self-subsistence farm production to khat: driving forces of change in Ethiopian agroforestry homegardens - Gebrehiwot, M.; Elbakidze, M.; Lidestav, G.; Sandewal, M.; Angelstam, P.; Kassa, H. (Cambridge University Press, 2016)
Traditional agroforestry homegardens deliver multiple products and benefits, including food security and livelihoods for rural households in Ethiopia. However, this land use has been changing towards monoculture production of khat (Catha edulis). This study analyses the development trajectories and causes of change in agroforestry homegardens. In total, 84 interviews, including key informant and semi-structured household interviews, and eight focus group discussions were conducted in the Southern Nations, Nationalities and Peoples' Regional State. It was found that khat production was increasing regardless of household wealth status. The proximate causes included better financial income for households, smaller sizes of farms due to farm land redistribution, favourable market conditions for khat, access to irrigation, decrease in governmental subsidies to buy fertilizer and quality seeds for food crop production, a positive experience of other farmers in khat production, and minimizing risks of theft and wildlife damage. Khat production challenges the implementation of national policies towards eradication of poverty and hunger.